KEPEMIMPINAN ADAPTIF YANG RELEVAN DITERAPKAN DALAM ORGANISASI TNI DI ERA VUCA: SUATU TINJAUAN LITERATUR - Windy Kartika Putri Widayanti; Asep Kusman (JURNAL ELEKTROSISTA, 2023)
This paper aims to examine adaptive leadership that is relevant to be applied in order to help TNI organizations, especially the Army, diagnose and prepare a conceptual framework to face adaptive challenges in an uncertain future, namely the VUCA (Volatile, Uncertain, Complex and Ambiguous) era. The research method used is the literature study method to explore adaptive leadership theories and practices that can potentially be applied in the Army environment. Literature database searches from various references including: books and data and research journals obtained from Scopus. The results of the analysis found that adaptive leadership is interpreted as the practice of mobilizing people to overcome difficult problems and challenges in order to bring about change in an organization. Adaptive leadership practices in New Zealand, South Africa and Indonesia have been formulated in the Adaptive Leadership Development Framework. From the Vos Viewer theme mapping, it is known that the 2012-2022 research literature study on adaptive leadership in the military is related to the topics: system, leader, study, change, challenge, practice, soldier, student and others. Furthermore, it is suggested that these topics be taken into consideration in formulating the formulation of the conceptual framework of the Adaptive Leadership Doctrine within the Indonesian Army.